Enhanced oral bioavailability of an etoposide multiple nanoemulsion incorporating a deoxycholic acid derivative-lipid complex - Saurav Kumar Jha; Hee-Soo Han; Laxman Subedi; Rudra Pangeni; Jee Young Chung; Seho Kweon; Jeong Uk Choi; Youngro Byun; Yong-Hee Kim; Jin Woo Park (Taylor & Francis Group, 2020)
In this study, a system for oral delivery of etoposide (ETP) was designed to avoid the problems associated with low and variable bioavailability of a commercially available ETP emulsion comprised of polyethylene glycol, glycerol, and citric acid anhydrous. ETP was complexed with low-molecular-weight methylcellulose (ETP/LMC) and loaded into a water-in-oil-in-water multiple nanoemulsion to formulate an ETP/LMC-nanoemulsion (ELNE). To further enhance the oral bioavailability, an ionic complex formed by anionic lipid 1,2-didecanoyl-sn-glycero-3-phosphate (sodium salt) and cationic Nα-deoxycholyl-l-lysyl-methylester was incorporated into ELNE, yielding ELNE#7. As expected, ELNE#7 showed 4.07- and 2.25-fold increases in artificial membrane and Caco-2/HT29-MTX-E12 permeability (Papp), respectively, resulting in 224% greater oral bioavailability compared with the commercially available ETP emulsion. In contrast, inhibition of clathrin- and caveola-mediated endocytosis, macropinocytosis, and bile acid transporters by chlorpromazine, genistein, amiloride, and actinomycin D in Caco-2/HT-29-MTX-E12 monolayers reduced the Papp by 45.0%, 20.5%, 28.8%, and 31.1%, respectively. These findings suggest that these routes play important roles in enhancing the oral absorption of ELNE#7. In addition, our mechanistic study suggested that P-glycoprotein did not have an inhibitory effect on the permeation of ELNE#7. Notably, ELNE#7 showed significantly enhanced toxicity in LLC and A549 cells compared with ETP-E. These observations support the improved oral absorption of ETP in ELNE#7, suggesting that it is a better alternative than ETP emulsion.